1907 N.J. Laws 116-17 - (:unkn) unknown (My University, 1907)
Ch. 62, 2: For greater certainty it is hereby specified that, in addition to the other powers hereby conferred upon said board, are the following: . . . To regulate and prohibit the use of guns, pistols, firearms and fireworks of all descriptions within the city.
Keywords: DISCHARGE